An examination on commuter's behavior and satisfaction level specifically on the impact of traffic congestion from UPV Iloilo City to SM City Iloilo - Abolucion, Chaneen; Alinsud, Danica; Parreño, John Terenz; Portillo, Jenele Awe; Vidal, Raphael Angelo; Villegas, Axel Joy
The study aims to examine the impact of traffic congestion to the commuting satisfaction and behavior of UPV Iloilo City Campus' students and employees as well as other significant factors. Using the Slovin's formula to do random sampling, the researchers gathered data from 146 respondents, 134 students and 12 staff or employees from University of the Philippines Visayas Iloilo City Campus with diverse socio-demographic characteristics. Futhermore, the researchers gathered additional data using the key informant interview (K11), as they scheduled a meeting and an interview with Transportation Management and Traffic Regulation Office (TMTRO). The paper attempts to determine how students' and employees' commuting satisfaction and behavior is affected by traffic congestion and how it relates to their overall commuting satisfaction. Upon the examination of the results, commuter's satisfaction do not vary significantly across different socio-demographic factors and traffic congestion indeed affects the commuter's satisfaction. The study could be used as a reference by the Local Governments Units (LGUs) and the TMTRO in the further improvement of traffic management and strategic management scheme in Iloilo City, specifically the route covered by UPV Iloilo City Campus to SM City Iloilo. Future researchers can also use this study as a reference about the impact of traffic congestion to the overall satisfaction of commuters among various socio-demographics. Lastly, future researchers can use this as a reference about commuters' behavior and lifestyle specifically in Iloilo City.